Does part-time work at school impact on going to university? - Gong, X.; Cassells, R.; Duncan, Alan (National Centre for Vocational Education and Training (NCVER), 2012)
Combining school study with part-time or casual work is an increasing trend for Australian high school students. For some, it is a way of earning some extra cash and having a bit of freedom from their parents, or it is an opportunity to get some experience in an occupation they are interested in. This paper looks at the impact that working while studying has on students’ intentions to go to university as well as their actual enrolments. The authors use data from the Longitudinal Surveys of Australian Youth (LSAY) 1998 cohort to observe the work and study patterns of young people over a period of time. The paper confirms the findings of other research: that students are more likely to combine study and work as they progress through their school years, with over half of students working in Year 12. The study also found that girls are more inclined to combine study and work, but boys tend to work more intensively than girls. Combining some work with study does not change the likelihood of enrolling in university, but working intensively - more than 15 hours per week - does reduce the chances of going to university, especially for girls. This paper adds new detail to what is emerging quite clearly: that some part-time work for full-time students is fine, but long hours do impact on academic progress.